BASIC COGNITIVE ASPECTUAL SEMANTICS - Mirsanov Gaybullo Qulmurodovich (International Journal of Literature and Language Studies, 2026)
Abstract. This study investigates aspectual semantics from the perspective of cognitive linguistics and prototype theory. The research focuses on the English stative verb to know and examines how its aspectual meanings are conceptualized in discourse. Drawing on the theoretical frameworks of Langacker, Jackendoff, and Geeraerts, the study analyzes the interaction between lexical semantics, aspectuality, and conceptual structure. The findings demonstrate that aspectual meaning is not restricted to grammatical markers but emerges through the interaction of cognitive, pragmatic, and contextual factors. The analysis further reveals that stative verbs possess a wider aspectual potential than traditionally assumed and can encode factual, resultative, and experiential meanings. The study contributes to the development of a cognitive approach to aspectual semantics and highlights the relevance of prototype structures in the interpretation of verbal meaning.